Introduction - Hausbacher, Eva; Parente-Čapková, Viola; Rosenholm, Arja; Sorvari, Marja Anneli (De Gruyter, 2026)
Introduction to the volume, which examines how women authors recall their own and their families’ past lives after having emigrated from the Soviet Union in the 1990s, and how they reflect on their new country of residence, be it Germany, Austria, Israel, USA, or Finland, among others. The Introduction explains the key concepts and the theoricomethodological background of the volum. It shows, how the individual chapters connect migration, memory, and gender studies to analyse literary presentations created by the "travelling" women whose work is analyzed in the book.
The Introduction exposes and theorizes the aim of the book, which is to pay attention both to women’s contribution to cultural transfer, and to the mobility of memories: for the first time, women’s narratives are brought up as a form and tool to work through both individual and collective traumas to the forefront, remedying a long-standing omission in Russian and post-Soviet migration history. The Introduction shows the ways in which the whole volume looks at "travelling" memories and cultural traumas from a gendered perspective, asking, what happens when the recollections of women’s traumatic experiences of Soviet history travel through time and space. Further on, the Introduction explains, how narratives by women who left the Soviet Union often call into question official accounts of Soviet history, rewriting them in a way that makes room for gendered lived experience.
Out of the USSR: Travelling Women – Travelling Memories